2020
DOI: 10.1002/anie.202004049
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling 79‐Year‐Old Ixene and Its BN‐Doped Derivative

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are key components of organic electronics. The electronic properties of these carbon‐rich materials can be controlled through doping with heteroatoms such as B and N, however, few convenient syntheses of BN‐doped PAHs have been reported. Described herein is the rationally designed, two‐step syntheses of previously unknown ixene and BN‐doped ixene (B2N2‐ixene), and their characterizations. Compared to ixene, B2N2‐ixene absorbs longer‐wavelength light and has a smaller ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 66 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…In this respect, the isosteric substitution of C=C bond with B-N bond is used to influence the electronic density and energy levels of corresponding frontier molecular orbitals (e.g., HOMOs and LUMOs) and hence to modulate molecular properties such as band gap, optoelectronic and catalytic properties [ 21 , 22 , 23 ]. However, the syntheses of BN-substituted PAHs are still in a dormant phase with only sporadic reports and the study of BN-PAHs cannot be further sustained for lack of enumerating stable BN-aromatic building blocks, albeit this contradiction in reality is a shock of startling [ 24 , 25 ]. Furthermore, the paramount challenges also come from the competence for orderly implementation of BN dipoles into the conjugate systems rather than some random choices, to precisely control both the orientation and quantity of the inserted BN dipoles.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the isosteric substitution of C=C bond with B-N bond is used to influence the electronic density and energy levels of corresponding frontier molecular orbitals (e.g., HOMOs and LUMOs) and hence to modulate molecular properties such as band gap, optoelectronic and catalytic properties [ 21 , 22 , 23 ]. However, the syntheses of BN-substituted PAHs are still in a dormant phase with only sporadic reports and the study of BN-PAHs cannot be further sustained for lack of enumerating stable BN-aromatic building blocks, albeit this contradiction in reality is a shock of startling [ 24 , 25 ]. Furthermore, the paramount challenges also come from the competence for orderly implementation of BN dipoles into the conjugate systems rather than some random choices, to precisely control both the orientation and quantity of the inserted BN dipoles.…”
Section: Introductionmentioning
confidence: 99%
“…Among the available methods for synthesizing 1,2‐azaborine containing PAHs, the electrophilic borylation, introduced by Dewar [2a] and optimized further, is attractive as both B−N and B−C bonds are constructed in one synthetic step (Scheme 1 a). [2h, 3a, 4] Alternatively, the coupling of carbon‐carbon (CC) bonds around existing BN units has occasionally been employed, e.g., by Piers, [5] Bonifazi, [3b, 6] and our group (Scheme 1 b). [7] The Wagner group [8] described the Au catalyzed NC bond formation as the final step of the synthesis of a doubly BN substituted perylene (Scheme 1 c).…”
Section: Methodsmentioning
confidence: 99%
“… Reagents and conditions: (a) 260 BBr 3 , i -Pr 2 EtN, o -DCB, 180 °C; (b) 261 PhBCl 2 , Et 3 N, 1,2,4-trichlorobenzene, reflux, 36 h; (c) Pd(OAc) 2 , PCy 3 , Cs 2 CO 3 , o -xylene, reflux, overnight. …”
Section: Pyrenoidsmentioning
confidence: 99%
“…In 2020, Park and Shin et al reported the preparation of B 2 N 2 -ixene ( 128.5 , Scheme 128 ). 261 The key precursor, 2,2′-(buta-1,3-diyne-1,4-diyl)dianiline ( 128.3 ), was obtained from the Glaser coupling of 2-ethynylaniline. Treatment of 128.3 with PhBCl 2 and Et 3 N brought about the chloroboration of alkyne followed by B–N bond formation to yield compound 128.4 in 28% yield.…”
Section: Pyrenoidsmentioning
confidence: 99%